Balancing Pedagogy, Emotions and Game Design in Serious Game Development - Natucci, Gabriel C.; Borges, Marcos A. F. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Serious games and game-based learning approaches have been shown to provide effective learning outcomes in various contexts. However, the design of games with educational purposes is not an easy feat, since many aspects must be considered during development: pedagogical theories, learning mechanics, game elements, player experience, and affective, cognitive and behavioral outcomes. The balance of these aspects is one of the greatest challenges both game designers and educators must face in the next few years, especially considering the impact of previously neglected areas, such as the importance of emotions in learning. This work outlines the complexities of this challenge and suggests possible solutions based on high-impact studies to create quality games that excel both in player experience and learning.